Improving of Insulation PS Materials With Smart PCL and Investigation of Some Physicochemical Properties of Their Blends - Kok, Mediha; Oner, Ecem Ozen; Coskun, Meltem; Pekdemir, Mustafa Ersin; Aydogdu, Yildirim (Wiley, 2025)
Polystyrene (PS) is a widely used polymer due to its low cost, lightweight nature, and ease of processing. However, its non-biodegradability poses significant environmental concerns. In this study, waste PS was blended with poly(epsilon-caprolactone) (PCL), a biodegradable smart polymer, to develop more sustainable polymeric materials. Blends with varying PS content were prepared and characterized using FTIR, differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and modulated DSC for heat capacity measurements. The PS-PCL blends exhibited shape memory behavior, particularly in compositions with higher PCL content, where the materials were able to recover their original shape upon thermal stimulation. Mechanical tests revealed that the addition of PCL significantly improved the flexibility and ductility of waste PS. Thermal analysis demonstrated enhanced thermal stability and increased heat capacity with rising PCL content. These findings suggest that blending waste PS with PCL is an effective strategy for improving its physicochemical properties, enabling both recycling and functional enhancement of PS-based materials.
Keywords: biopolymers and renewable polymers; blend; differential scanning calorimetry (DSC); heat capacity; shape memory effect; smart material; thermal properties; thermogravimetric analysis (TGA); thermoplastics; waste polystyrene